Survey of Gravitationally lensed Objects in HSC Imaging (SuGOHI) – V. Group-to-cluster scale lens search from the HSC–SSP Survey. Issue 1 (21st April 2020) - Jaelani, Anton T; More, Anupreeta; Oguri, Masamune; Sonnenfeld, Alessandro; Suyu, Sherry H; Rusu, Cristian E; Wong, Kenneth C; Chan, James H H; Kayo, Issha; Lee, Chien-Hsiu; Chao, Dani C-Y; Coupon, Jean; et al.
ABSTRACT: We report the largest sample of candidate strong gravitational lenses belonging to the Survey of Gravitationally lensed Objects in HSC Imaging for group-to-cluster scale (SuGOHI-c) systems. These candidates are compiled from the S18A data release of the Hyper Suprime-Cam Subaru Strategic Program (HSC–SSP) Survey. We visually inspect ∼39 500 galaxy clusters, selected from several catalogues, overlapping with the Wide, Deep, and UltraDeep fields, spanning the cluster redshift range of 0.05 < z cl  < 1.38. We discover 641 candidate lens systems, of which 536 are new. From the full sample, 47 are almost certainly bona fide lenses, 181 of them are highly probable lenses, and 413 are possible lens systems. Additionally, we present 131 lens candidates at galaxy scale serendipitously discovered during the inspection. We obtained spectroscopic follow-up of 10 candidates using the X-shooter. With this follow-up, we confirm eight systems as strong gravitational lenses. Of the remaining two, one of the sources is too faint to detect any emission, and the other has a tentative redshift close to the lens redshift, but additional arcs in this system are yet to be observed spectroscopically. Since the HSC–SSP is an ongoing survey, we expect to find ∼600 definite or probable lenses using this procedure and even more if combined with other lens finding methods.